A Simple and Efficient Supramolecular Chemistry Approach for Synthesis of Bis(indolyl)methanes Using Aqueous β-Cyclodextrin as Green Promoter Host - Shaikh, Sameer I.; Zaheer, Zahid; Mokale, Santosh N. (Letters in Organic Chemistry, 2018)
Background: In the recent years, various bis-heterocyclic compounds are reported for their varied biological activities. Bis(indolyl)methanes and its derivatives are commonly present in over 3000 natural isolates and reported for its broad spectrum of biological activities. Though, there are so many methods reported for the synthesis of bis(indolyl)methanes, there is a need to develop a green and ecofriendly synthetic protocol which in turn is important for economic and synthetic point of view. Method: The supramolecular chemistry approach was efficiently used for the synthesis of bis(indolyl)methane derivatives 3(a-o) by the condensation reaction of indole 1 (2.0 mmol) and substituted aldehydes 2(a-o) (1.0 mmol) at 60°C using β-cyclodextrin in water. The progress of the reaction was monitored by TLC using ethyl acetate:hexane (7:3) as a mobile phase. The identity and purity of the products were confirmed by MASS, 1H NMR, and 13C NMR. Results: This report describes supramolecular synthesis of bis(indolyl)methanes 3(a-o) using β-cyclodextrin (1.0 mol%) in water at 60°C. The synthesized compounds 3(a–o) were obtained in excellent yields (80-92 %) in less reaction time (20-40 min). The hydrophobic binding of β-cyclodextrin with one of the reactants is explained by 1H NMR. The rate of the reaction is accelerated if electron withdrawing groups like Cl and F are present on the aromatic ring. Conclusion: We have efficiently synthesized bis(indolyl)methanes 3(a–o) via threecomponent one-pot condensation reaction of indole with substituted aldehydes using β-cyclodextrin as a supramolecular catalyst in aqueous medium. β-cyclodextrin is biodegradable, recoverable and purely environmentally benign. This method has several advantages over existing catalytic protocols as it has simple and green experimental procedures, use of green reaction media (water), lower reaction time, high reaction rate and avoids cumbersome work-up.
Keywords: green promoter